2012
DOI: 10.1080/15332969.2012.662457
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Airlines—A New Customer Relationship? An Analysis of Service Quality, Service Satisfaction, and Customer Loyalty in a Low-Cost Setting

Abstract: ABSTRACT. Many organizations are now paying close attention in evaluating and implementing marketing strategies with the specific aim of improving customer retention. While extensive literature has focused on the link between service quality, satisfaction, and loyalty, little research has been conducted on examining these three constructs in the context of low cost airlines. Using questionnaire data collected at two European airports, the results suggest that though both the service quality and customer satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 32 publications
2
41
0
3
Order By: Relevance
“…Customers that have received better service cues, such as comfortable seats, friendly flight attendants, and quality food and beverages, during the flight, perceived a higher level of service quality (Kaynak, Kucukemiroglu, and Kara ; Mikulić and Prebežac ; Young, Cunningham, and Lee ). The findings of this study support the literature suggesting that customers who receive better ground services, such as easy check‐in and boarding processes, effective baggage handling, and on‐time flights, will perceive better service quality (Curry and Gao ; Gilbert and Wong ; Kaynak, Kucukemiroglu, and Kara ). The results showed that the greatest difference in PSQ between United Airlines and Continental Airlines before the merger was due to their ground services.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Customers that have received better service cues, such as comfortable seats, friendly flight attendants, and quality food and beverages, during the flight, perceived a higher level of service quality (Kaynak, Kucukemiroglu, and Kara ; Mikulić and Prebežac ; Young, Cunningham, and Lee ). The findings of this study support the literature suggesting that customers who receive better ground services, such as easy check‐in and boarding processes, effective baggage handling, and on‐time flights, will perceive better service quality (Curry and Gao ; Gilbert and Wong ; Kaynak, Kucukemiroglu, and Kara ). The results showed that the greatest difference in PSQ between United Airlines and Continental Airlines before the merger was due to their ground services.…”
Section: Discussionsupporting
confidence: 83%
“…Airline merger, as the independent variable, was measured as a dummy variable with three values: 0 for postmerger United Airlines; 1 for premerger United Airlines; and 2 for Continental Airlines. We measured the dependent variables using 22 items in the research questionnaire via a 7‐point Likert scale ranging from “1 = Strongly Disagree” to “7 = Strongly Agree.” Similar to Curry and Gao (), this study considered PSQ in airlines a reflective second‐order construct, including three dimensions of flight experience ( α = .79), airport experience ( α = .82), and perceived safety ( α = .84)—each measured using four items adapted from previous literature on airline services (Mikulić and Prebežac ; Oyewole ; Ringle, Sarstedt, and Zimmermann ). Perceived service value ( α = .91) was measured using three items adapted from the consumer value literature (Agarwal and Kenneth Teas ; Sweeney and Soutar ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…-the impact of airline service quality and comfort on passenger choices (Balcombe, Fraser, & Harris, 2009;Jiang, 2013;Martin, Roman, & Espino, 2008;Park, Robertson, & Wu, 2004;Park, Robertson, & Wu, 2004Wojahn, 2002;Jiang, 2012;Pennig, Quehl, & Rolny, 2012;Wojahn, 2002;Yang, Hsieh, Li, & Yang, 2012;Zhang Y., Zhang, 2012); -the attributes of the airline service quality (Babbar & Koufteros, 2008;Curry & Gao, 2012;De Jager, Van Zyl, & Toriola, 2012;Kim & Lee, 2009;Martin, Roman, & Espino, 2011;Wen & Yeh, 2010) and the customer-value drivers (Boetsch, Bieger, & Wittmer, 2011;Park, Robertson, & Wu, 2009); -the evaluation of airline service quality (Chen & Chang, 2005;Cheng & Chang, 2006;Chou, Liu, Huang, Yih, & Han, 2011;Higgins, Lawphongpanich, Mahoney, & Yin, 2008;Liou & Tzeng, 2007;Pakdil & Aydin, 2007;Tsaur, Chang, & Yen, 2002); -the effect of service quality on airlines' performance (Sim, Koh, & Shetty, 2006), the proposal of methods and strategies for improving airline service quality (Liou, Tsai, Lin, & Tzeng, 2011;Liou, Yen, & Tzeng, 2010;Maji, 2012);…”
Section: A Model Model For Aircraft Evaluation Aircraft Evaluation Tomentioning
confidence: 99%